Precarious Lifes and Vulnerable Bodies in María Reimóndez’s Cobiza (2021) - Moszczyńska-Dürst, Katarzyna (Madrygal. Revista de Estudios Gallegos, 2023)
Posthumanismand ecofeminism abandon the notion of representing a universal subject and question the phallogocentric and humanist paradigm of the symbolic order. Subjectivity becomes ex-centric, nomadic, animalistic (both personal and communal). Embodiment and performativity are seen as indispensable conditions that situate one’s own experience in relation to the experience of others and in terms of a collective agency. This, in turn, allows for the redefinition of certain naturalised narratives in relation to agency, materiality, nature, gender and the body; those schools of thought focus on precarious and vulnerable lives, both human and non-human. Science fiction has become prominent in creating, rewriting and debating the theoretical and political positions mentioned above. Hence, the aim of this article is to analyse Cobiza (2021), María Reimóndez’s recent dystopian novel, in light of ecofeminism and posthumanism. It focuses also on the means by which the novel participates in the social and political production and reproduction of subjectivities marked by exclusion and estrangement, and embodied in the figures of pariahs and defectors.